SURVEY OF SEROPOSITIVE RATE FOR TOXOCARA SPP. LARVAE AND RELATED FACTORS AT MILITARY HOSPITAL 175 IN 2025 (Vietnam Journal of Community Medicine, 2026)
Toxocariasis is a parasitic disease transmitted from animals to humans caused by Toxocara spp. larvae. In Vietnam, favorable climatic conditions and free-range dog/cat keeping contribute to increased risk of exposure to the disease.Objective: To determine the seroprevalence rate for Toxocara spp. larvae and the relationship between seroprevalence test results for Toxocara spp. and factors related to knowledge and behavior of participants at Military Hospital 175.Subjects and methods: Cross-sectional study on 221 outpatients, who were assigned to ELISA test for IgG antibodies against Toxocara spp. and answered a questionnaire.Results: The seroprevalence rate for Toxocara spp. larvae was 55.2%. There was a statistically significant association between positive serological results and occupation (p=0.03), frequency of dog/cat contact (p=0.008), and soil contact (p
Keywords: Toxocara spp, ELISA IgG, The serological rate of Toxocara spp